Business schools for impact : teaching skills to build Base of Pyramid businesses (UN New YorkUS, 2015)
Explains how business schools can contribute to sustainable development in the poorest areas in the world by changing the mindset of business graduates and teaching the skills required to invest and operate in low-income environments with positive social impact.
Keywords: BUSINESS